Testosterone and estradiol differentially affect cell proliferation in the subventricular zone of young adult gonadectomized male and female rats. (12th February 2015) - Farinetti, A.; Tomasi, S.; Foglio, B.; Ferraris, A.; Ponti, G.; Gotti, S.; Peretto, P.; Panzica, G.C.
Graphical abstract: Highlights: Adult gonadectomy reduces cell proliferation in male but not in female rat SVZ. Testosterone or estradiol, but not DHT restores cell proliferation only in male rats. Adult neurogenesis in rats is a process differentially modulated in the two sexes. Abstract: Steroid hormones are important players to regulate adult neurogenesis in the dentate gyrus of the hippocampus, but their involvement in the regulation of the same phenomenon in the subventricular zone (SVZ) of the lateral ventricles is not completely understood. Here, in male rats, we tested the existence of activational effects of testosterone (T) on cell proliferation in the adult SVZ. To this aim, three groups of male rats: castrated, castrated and treated with T, and controls were treated with 5-bromo-2′-deoxyuridine (BrdU) and killed after 24 h. The density of BrdU-labeled cells was significantly lower in castrated animals in comparison to the other two groups, thus supporting a direct correlation between SVZ proliferation and levels of circulating T. To clarify whether this effect is purely androgen-dependent, or mediated by the T metabolites, estradiol (E2 ) and dihydrotestosterone (DHT), we evaluated SVZ proliferation in castrated males treated with E2, DHT and E2  + DHT, in comparison to T- and vehicle-treated animals, and sham-operated controls. The stereological analysis demonstrated that E2 and T, but not DHT, increase proliferation in the SVZ of adult male rats. Quantitative evaluation of cells expressing the endogenous marker of cell proliferation phosphorylated form of Histone H3 (PHH3), or the marker of highly dividing SVZ progenitors Mash1, indicated the effect of T/E2 is mostly restricted to SVZ proliferating progenitors. The same experimental protocol was repeated on ovariectomized female rats treated with E2 or T. In this case, no statistically significant difference was found among groups. Overall, our results clearly show that the gonadal hormones T and E2 represent important mediators of cell proliferation in the adult SVZ. Moreover, we show that such an effect is restricted to males, supporting adult neurogenesis in rats is a process differentially modulated in the two sexes.